FEATURES OF TAX SYSTEM IN CANADA - L. D. Efanova; T. A. Sukhacheva (Вестник университета)
The state of Canada’s tax system has been studied. The structure of taxation in Canada, in particular current issues of tax control over taxpayers, have been considered. In the course of the study, regulative, complex methods of studying the tax system in Canada, general scientific and special methods of scientific knowledge: systematic and functional-structural, comparative analysis were used. It has been revealed that the tax system in Canada is more sparing and effective then in other countries. Canada, unlike other developed countries, has a higher degree of decentralization, when, with a significant impact of federal authorities, the provinces play a significant role in the formation of the concept of the national economy. This state is able to provide its citizens with a high standard of living, decent wages and quite loyal tax system.